ABii at School: Findings from a Long-Term In-School Field Study with a Commercial Robot-Assisted Learning System - Chen, Lujie Karen; Daughrity, LeaAnne; Sakowicz, Marie; Hamidi, Foad; Godwin, Karrie E.; Lipsmeyer, Lin Lin (Nature, 2025)
Although there is growing evidence of the potential value of physically present educational robots in improving engagement and learning outcomes with young children, there is limited understanding of how those effects may play out over an extended period in a real school environment. There is also sparse literature on students’ and teachers’ experiences and perspectives with a robot-assisted learning system deployed at school. In this paper, we report a two-phase pilot study using a commercially available robot-assisted learning system ABii from Van Robotics with 24 students from two early childhood classrooms in a resource-constrained urban public school on the east coast of the US. The first phase was a researcher-directed pilot that ran for eight weeks, followed by a second phase of a teacher-directed pilot that lasted five months, where teachers were empowered to take charge of the robot usage in their classrooms. We reported the findings concerning students’ and teachers’ experience and perspectives with the systems using a combination of quantitative data from the system logs and qualitative data from observation and interviews. We observed positive effects of the physically present robot, as students maintained sustained interest and engagement with ABii even after eight weeks of use. Teachers likewise valued ABii’s role in supporting engagement and delivering personalized learning experiences—benefits that were particularly meaningful in resource-constrained environments, despite certain challenges associated with deploying physical robots. Moreover, our findings highlight the essential role of teachers in the successful integration of advanced technologies such as educational robots, suggesting that human teachers remain central to realizing educational robots’ full pedagogical potential. We discuss the implication of those findings by reflecting on the current literature on educational social robots and articulating their contribution to the empirical understanding of the potential value and challenges in leveraging robot-assisted learning systems with young children in under-resourced school environments.
Keywords: UMBC Child Development Lab; Field study; Social robot for learning; Long-term study; Engagement; UMBC Human-Centered Computing Program; UMBC Lab for Informatics for Human Flourishing; Personalized learning